Seasonal dynamics of productivity of piglets at growing them in pens with different type of floor - Повод, М. Г.; Шпетний, М. Б. (Scientific Progress & Innovations, 2018)
The seasonal dynamics of piglets’ productivity was studied at growing them in the pens with polymeric and concrete perforated floors. The dependence of piglets’ productivity on growing from the type of perforated floor in the pen was determined all the time of the year. In winter, piglets that were growing with replacement in the pen polymer perforated floors on concrete, daily consumed per each by 13.8 % less feed, had 18.4 % lower than the daily average, 18.5 % absolute and 10.2 % relative increase, resulting in a decrease by 13.1 % of live weight at its completion. They also had a worse feed conversion by 5.0 % and 5.9 % piglet survival than their counterparts who were kept in pens with a polymeric perforated floor. Spring piglets that growing on a perforated concrete floor were on 7.8 % lower in weight, they found 10.9 % lower average daily, 10.9 % absolute and relative 6.1 % increase in body weight. They consumed less than 7.7 % of food each day, had a 3.5 % worse conversion than their peers, who were grown on a polymeric perforated floor. In summer the difference between piglets, which were kept on the concrete and polymer perforated floors, was for the average daily gains of 5.7 %, absolute growth – 11.0 %, relative growth – 4.8 %, feed conversion – 3.2 %, preservation – 3.0 % in favor of animals, which were kept on the polymer floor. They consumed 9.0 % less feed daily and had 8.4 % less weight at the end of growing period. In autumn animals that were grown on the concrete floor daily consumed by 12.0 % less feed, had 15.4 % lower average daily, 15.5 % absolute and 7.8 % relative gains, 4.0 % lower feed conversion and by 4.0 % lower piglets survival and at the end of growing period had a smaller by 9.1 % live weight.